TINDAK TUTUR DALAM LIRIK LAGU SORAI KARYA NADIN AMIZAH: STUDI PSIKOPRAGMATIK - Asyanti, Asyanti (FKIP Universitas Lampung, 2023)
The song Sorai sung by Nadin Amizah tells about the meaning of a breakup. This song was created on the basis of the personality of Nadin Amizah who wanted to express that sadness does not always refer to sadness. Nadin pointed out that parting also means happiness, beautiful farewells, and letting go of one another. The purpose of this study is to describe the speech acts in the lyrics of Sorai's song which convey the meaning of the word